German Language in The Aspect of Interlingual Communication - Rakhimova Muyba Temirovna (Genius Publishing Group, 2022)
The article is based on the materials of own observations, as well as reporting and statistical data of recent years on the use of the German language in the scientific and educational space of the named non-linguistic university. .The purpose of this article is to analyze the state of affairs with the teaching of the German language in a non-linguistic university by identifying problems, opportunities and prospects for its study . As you know, the status of the German language, as well as a number of other foreign languages, has undergone significant changes in the scientific and educational space of recent decades, which have led to a reduction in the opportunities for its study and application both in linguistic and - non linguistic universities.
Keywords: foreign language; nonlinguistic; additional efforts